2012
DOI: 10.1177/0891241612458954
|View full text |Cite
|
Sign up to set email alerts
|

Sober as Deviant

Abstract: Social scientists have conducted numerous studies on college students’ binge drinking behavior. They have not, however, conducted any systematic studies of nondrinkers on college campuses. Our study focuses on the everyday experiences of nondrinking undergraduates who stay “dry” while living on “wet” campuses. We use the symbolic interactionist notions of identity work and deviance to show how nondrinkers employ a variety of stigma management strategies to avoid being labeled deviant. These strategies include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 63 publications
(88 reference statements)
5
16
0
Order By: Relevance
“…Consistent with studies of college student non-drinkers (Herman-Kinney & Kinney, 2013;Romo, 2012), this investigation's participants generally did not bring up their non-drinking status proactively. But when offered a drink, non-drinkers adopted one or more of the following politeness strategies: bald on record (often combined with positive politeness), off-record, and avoid the FTA (Brown & Levinson, 1987).…”
Section: How Non-drinkers Communicatively Negotiated Their Non-drinkisupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with studies of college student non-drinkers (Herman-Kinney & Kinney, 2013;Romo, 2012), this investigation's participants generally did not bring up their non-drinking status proactively. But when offered a drink, non-drinkers adopted one or more of the following politeness strategies: bald on record (often combined with positive politeness), off-record, and avoid the FTA (Brown & Levinson, 1987).…”
Section: How Non-drinkers Communicatively Negotiated Their Non-drinkisupporting
confidence: 82%
“…Through interviews with nondrinking college students, Herman-Kinney and Kinney (2013) and Romo (2012) found that abstaining from alcohol in college violated social norms. By not drinking, most college student abstainers reported experiencing felt and enacted stigma, which they deliberately managed (Herman-Kinney & Kinney, 2013;Romo, 2012). Some students concealed their non-drinking identity, passing as a drinker by holding what appeared to be an alcoholic drink, by acting drunk, or by smelling of alcohol (Herman-Kinney & Kinney, 2013;Romo, 2012).…”
Section: Review Of the Non-drinking Literaturementioning
confidence: 93%
See 3 more Smart Citations